Efektivitas Model Contence Muzzle Dalam Pembelajaran Keterampilan Menulis Pada Kelas III Sekolah Dasar - Nunung Dwi Utami; Akhmad Arif Musadad; Leo Agung Sutimin (Universitas Sebelas Maret, 2017)
Indonesian Language Learning in Primary Schools basically consists of four competencies, namely listening (listening), speaking, reading and writing. The purpose of this study is 1) to determine the effectiveness level of the Contour Muzzle model in learning to write seen from cognitive value, 2) to determine the effectiveness level of the Contence Muzzle model in learning to write viewed from the affective value, 3) to find out the effectiveness level of the Contence Muzzle model in learning writing seen from the psychomotor value. This type of research is quantitative research with experimental methods (posttest only control group design). Research subjects included third-grade students in elementary schools in Tirtomoyo District who were chosen randomly. Data collection techniques using data/source triangulation and method triangulation, obtained from data on student performance scores. Data analysis was performed with parametric statistics if they met normal and homogeneous and non-parametric requirements if both conditions were not met. Tests carried out with a significance level of 0.05%. The results of this study indicate that (1) there is a difference between the average cognitive value of the experimental class and the control class of 10.67%, (2) there is a difference between the average value of the experimental class and the control class of 82.21%, ( 3) there is a difference between the average psychomotor value of the experimental class and the control class by 16.73%